2015
DOI: 10.1007/s00467-014-3038-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of therapeutic plasmapheresis in ANCA-associated vasculitis

Abstract: Plasma exchange, or plasmapheresis, is a treatment method that developed over a period of two decades and involves the removal and replacement of a patient's circulating plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…In clinical daily practice, adding plasma exchange in the treatment of RPGN or diffuse alveolar hemorrhage improved the outcome . The eight randomized trials and the Cochrane Systematic Review reported that plasma exchange in severe AAV may be effective in reducing the development of ESRD by approximately 40% .…”
Section: Discussionmentioning
confidence: 99%
“…In clinical daily practice, adding plasma exchange in the treatment of RPGN or diffuse alveolar hemorrhage improved the outcome . The eight randomized trials and the Cochrane Systematic Review reported that plasma exchange in severe AAV may be effective in reducing the development of ESRD by approximately 40% .…”
Section: Discussionmentioning
confidence: 99%
“…While plasmapheresis is more often used to treat cryoglobulinemia, it is only used in cases of severe renal failure requiring hemodialysis and/or pulmonary hemorrhage in ANCA disease [29, 30]. Given these differences, we recommend that HCV-infected patients with positive ANCA serologies should be thoroughly examined for other possible systemic manifestations, and that they undergo renal biopsy in order to confirm the presence of ANCA-associated GN, with or without coexisting cryoglobulinemic vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…The other option tried in this patient was antibody immune-adsorption via PLEX which has been demonstrated to be safe and well tolerated in pregnant women when used for other conditions [ 11 ]. Evidence thus far has shown some benefit of this therapy in AAV; however, many key questions remain unanswered [ 12 ]. Agents not tried in our patient included azathioprine (AZA) and rituximab (RTX).…”
Section: Discussionmentioning
confidence: 99%